Navigating the Written Path: Exploring Current Trends in Medical Writing - Mitesh Mohan Hood (Medical Research and Its Applications Vol. 7, 2024)
Medical writing is a significant link between science and communication. It plays a vital role amid complex medical information and diverse audiences. As the healthcare landscape evolves, so does the practice of medical writing. This article explores the current trends shaping the field of medical writing, from advancements in technology such as the adoption of AI and ML algorithms to changes in regulatory standards of the agencies, such as the FDA in the United States and the EMA in Europe as well as the evolving role of patient-centered communication. By navigating these trends, medical writers can effectively communicate critical information, drive informed decision-making, and ultimately improve healthcare outcomes.